Evaluation of Liquid-Liquid Extraction and Different Solid Phase Extraction Cartridges for Determination of Selected Synthetic Pyrethroid Insecticides in Whole Blood - Yavuz, O.; Aksoy, A.; Das, Y.K.; Atmaca, E. (Asian Journal of Chemistry, 2010)
In this study, the comparison of classical liquid-liquid extraction (LLE) and different solid phase extraction (SPE) cartridges for determination of some synthetic pyrethroid insecticides in whole blood was aimed. Six synthetic pyrethroids (α-cypermethrin, permethrin, S-bioallethrin, cyphenothrin, cyfluthrin and tetramethrin) were spiked at three different concentration levels (250, 500 and 1000 ng/mL) in 1 mL rabbit blood and each dilution of the insecticides was applied classical LLE and three different SPE procedures (florisil, C18 and silica). Final solutions were analyzed with gas chromatography equipped with electron capture detector. Detection limits of the insecticides were found between 3.55 and 16.55 ng/mL. Recovery percentages were determined generally higher than 100 % and matrix effect was observed in LLE procedures of all pyrethroids. Solid phase extraction cartridges decreased this failure and SPE applications may evaluate beneficial for synthetic pyrethroid analysis in whole blood. However, the reduction of the matrix effect was occurred different grades for used SPE cartridges and it was insuffi-cient in some procedures. Florisil cartridges were determined better than the other sorbents for providing good recoveries. This study may be analytical data for pyrethroid analysis using combinations of classical LLE and different SPE sorbents. It was also concluded that further studies should be performed with different LLE procedures and solutions of elution and extraction for determination of the optimal technique.